Range expansion of Kuhl’s pipistrelle (Pipistrellus kuhlii) into Belarus - Shpak, A.; Larchenko, A. (Праці теріологічної школи, 2016)
The history and directions of the expansion of Kuhl’s pipistrelle (Pipistrellus kuhlii (Kuhl, 1817) in Russia, Ukraine and Central Europe from the second half of the 20th century to the present time is analyzed. Data on records of Kuhl’s pipistrelle in Belarus are presented. It is assumed that, initially, the invasion of P. kuhlii into Belarus occurred from the eastern center of its distribution (Azerbaijan) and range expansion will take place in northwest direction along the rivers of the Dnipro and Prypiat basins. Colonization of the western part of Belarus from northwestern Ukraine is highly expected.